Construction of atrial fibrillation‐related circRNA/lncRNA‐miRNA‐mRNA regulatory network and analysis of potential biomarkers - Wen, Jia‐le; Ruan, Zhong‐bao; Wang, Fei; Chen, Ge‐cai; Zhu, Jun‐guo; Ren, Yin; Zhu, Li (Journal of clinical laboratory analysis, 2023)
Background The specific pathogenesis of atrial fibrillation (AF) remains unclear. In this study, we examined the expression of differential messenger RNAs (mRNAs), circular RNAs (circRNAs), and long‐stranded noncoding RNAs (lncRNAs) from human peripheral blood mononuclear cells to initially construct a circRNA/lncRNA‐miRNA‐mRNA ceRNA regulatory network to explore the pathogenesis of AF and to screen for potential biomarkers. Methods A total of four pairs of AF cases and healthy subjects were selected to detect differentially expressed mRNAs, circRNAs, and lncRNAs in peripheral blood mononuclear cells by microarray analysis. And 20 pairs of peripheral blood from AF patients and healthy subjects were selected for validation of mRNA, circRNA, and lncRNA by quantitative real‐time PCR (qRT‐PCR).The relevant ceRNA networks were constructed by GO and KEGG and correlation analysis. Results The results showed that compared with healthy subjects, there were 813 differentially expressed mRNAs (DEmRNAs) in peripheral blood monocytes of AF, including 445 upregulated genes and 368 downregulated genes, 120 differentially expressed circRNAs (DEcircRNAs), including 65 upregulated and 55 downregulated, 912 differentially expressed lncRNAs (DElncRNAs), including 531 upregulated and 381 downregulated lncRNAs. GO and KEGG analysis of DERNA revealed the biological processes and pathways involved in AF. Based on microarray data and predicted miRNAs, a ceRNA network containing 34 mRNAs, 212 circRNAs, 108 lncRNAs, and 38 miRNAs was constructed. Conclusion We revealed a novel ceRNA network in AF and showed that downregulated XIST, circRNA_2773, and CADM1 were negatively correlated with miR‐486‐5p expression and had a potential targeting relationship with miR‐486‐5p. The ceRNA regulatory network of circRNA/lncRNA‐miRNA‐mRNA was preliminarily constructed to explore the pathogenesis of AF and screen potential biomarkers.